INVESTIGATING THE ROLES OF METABOLIC ENZYMES IN INSECTICIDE RESISTANCE IN THE Culex pipiens sensu lato POPULATION FROM GOMBE NIGERIA - N, ABUBAKAR; S. K, HAMIDU (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2023)
Despite the widespread reports of insecticide resistance in the arboviral vectors in Gombe state, the direct role of metabolic enzymes in such resistance is sparse. This study aimed to determine if some metabolic enzymes play a role in the resistance to insecticides in the population of Cx pipiens from Gombe State. The adult female Cx pipiens were picked randomly and categorized into “Exposed” and “Unexposed” groups. The Exposed group was treated with Fenitrothion or Bendiocarb insecticides for 30 min using a WHO bioassay tube while the Unexposed group was exposed to a plane paper using a similar method. The Glutathione-S-transferases (GSTs), alpha-esterases, and beta-esterases activities of 31 mosquitoes from both groups were determined using the biochemical assay protocol. The mean enzyme activity of Unexposed was slightly higher (35.64 nmol-1min-1mg) compared to the Exposed (34.89 nmol-1min-1mg) in the alpha-esterases but lower (34.69 nmol-1min-1mg) in beta-esterases than Exposed (35.93 nmol-1min-1mg). However, Unexposed (14.11nmol-1min-1mg) exhibited higher mean activity than the Exposed (12.93 nmol-1min-1mg) in GSTs but not to a significant extent. The insecticide exposure appeared to slightly elevate the activity of beta-esterases while moderately reducing the activity of alpha-esterases and GSTs in the Exposed group. The decrease in enzyme activity in the Exposed but not in the Unexposed group might indicate the involvement of these enzymes in the resistance to the 30 min insecticides exposure. Thus, although not to a significant level, alpha-esterases and GSTs appeared to be involved. Since no statistically significant difference (P<0.05) in enzyme activity between the two groups in all 3 enzymes was observed, we, therefore, conclude that the three metabolic enzymes do not seem to be majorly responsible for the insecticide resistance in these populations. we suggest that monooxygenases or target site mutations such as kdr L1014F may be involved.